2022
DOI: 10.3390/bs12080262
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression: What Do We Know of Neuropeptides?

Abstract: In modern society, there has been a rising trend of depression and anxiety. This trend heavily impacts the population’s mental health and thus contributes significantly to morbidity and, in the worst case, to suicides. Modern medicine, with many antidepressants and anxiolytics at hand, is still unable to achieve remission in many patients. The pathophysiology of depression and anxiety is still only marginally understood, which encouraged researchers to focus on neuropeptides, as they are a vast group of signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 350 publications
0
26
0
Order By: Relevance
“…The hypothalamicpituitary-adrenal (HPA) axis is another putative target for neuropeptides relevant to the regulation of stress response in the context of altered mood, emotion and aggressive behavior [24,25]. Among the neuropeptides reviewed recently for their implication in anxiety and depression, we do not find 26RFa [26,27]. This lack, however, does not mean that 26RFa has no role in emotional regulation but is explained by the fact that only a few studies with relevant data are available.…”
Section: Discussionmentioning
confidence: 55%
“…The hypothalamicpituitary-adrenal (HPA) axis is another putative target for neuropeptides relevant to the regulation of stress response in the context of altered mood, emotion and aggressive behavior [24,25]. Among the neuropeptides reviewed recently for their implication in anxiety and depression, we do not find 26RFa [26,27]. This lack, however, does not mean that 26RFa has no role in emotional regulation but is explained by the fact that only a few studies with relevant data are available.…”
Section: Discussionmentioning
confidence: 55%
“…This metabolic environment directly stimulates the pain receptors of the thalamus, or indirectly, via the glial cells of the diencephalon, creating a situation of central sensitization with systemic inflammation and pain (neuroinflammation) [ 15 , 21 ]. Substance P is one of the molecules involved in depression and anxiety, and in cognition [ 22 , 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…74,75 In animal models, its administration can elicit depressive and anxious behaviors. 74,75 Elevated levels of SP have also been observed in individuals with MDD compared to healthy controls, and levels subsequently drop after they receive treatment for depression. 74 Finally, high BDNF levels in AD patients have been correlated with disease activity, potentially due to its immunomodulatory effects including chemotaxis, inhibition of eosinophil apoptosis, and localization of eosinophils to sensory nerve fibers.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…74,75 Elevated levels of SP have also been observed in individuals with MDD compared to healthy controls, and levels subsequently drop after they receive treatment for depression. 74 Finally, high BDNF levels in AD patients have been correlated with disease activity, potentially due to its immunomodulatory effects including chemotaxis, inhibition of eosinophil apoptosis, and localization of eosinophils to sensory nerve fibers. 76,77 Yeom et al reported that anxious and depressive-like behavior in AD mice was associated with increased BDNF striatal levels and activation in the reward circuitry.…”
Section: Atopic Dermatitismentioning
confidence: 99%